Enhanced stabilisation and methane potential of MSWs in a field-scale landfill with leachate recirculation. (11th May 2004) - Ozkaya, B.; Demir, A.; Bilgili, M.S.
This study was carried out on two field scale test cells constructed at Odayeri Sanitary Landfill (OSL) located at the European side of Istanbul city. Approximately 11, 000 tons of municipal solid wastes (MSW) were filled at equal quantities to each cell (C1 and C2). Leachate was periodically recirculated to one (C2) of the test cells in various quantities. These cells are compared in terms of leachate quality (pH, BOD and COD), methane potential (MP) of wastes and surface settlement for a monitoring period of 0–400 days. Experimental results showed that optimum pH for anaerobic decomposition was reached in a shorter period of time in C2 compared to C1. Moreover, BOD and COD concentrations were decreased more rapidly in C2 cell than in C1 cell. BOD/COD ratio was determined as 0.25 and 0.17 for C1 and C2 cells consequently after 380 days from placement of refuse to the test cells. In MP tests, first order rate constants for cell C1 and C2 were found be 0.145 year -1 and 0.222 year -1, respectively. Topographic measurements revealed that cumulative settlements after 12 months from refuse placement were 0.49 and 0.70 m for C1 and C2 cells, respectively. According to results obtained from this study, it can be concluded that appropriate conditions can cause enhance in the decomposition rate of MSW.